Self-reported service needs and barriers reported by autistic adults: Differences by gender identity - Koffer Miller, Kaitlin H.; Cooper, Dylan S.; Song, Wei; Shea, Lindsay L. (Research in autism spectrum disorders, 2022)
•Other gender autistic adults reported more service needs than autistic men.•Autistic women and other gender adults experienced more service barriers.•Barriers to service access include transportation, cost, and availability.•Only other gender autistic adults experienced unmet needs for counseling services. Autism spectrum disorder (ASD) is a lifelong disorder that is diagnosed nearly four times as frequently in men than women. Gender distinctions are evolving beyond traditional man and woman binaries. It remains unclear if and how these distinctions may impact autistic individuals. The goal of this research was to examine reported service needs and barriers to accessing services among autistic adults by gender identity (man, woman, and other gender). Data were generated from a statewide needs assessment survey that included quantitative and qualitative data collection that identified the needs of autistic individuals of all ages and their family members and caregivers. The results of this study are among the first to document barriers to service access reported by autistic adults across men, women, and other gender adults. This study also found that other gender autistic adults were more likely to report unmet needs for counseling services than autistic men, and both autistic women and other gender adults in this sample reported multiple barriers to receiving needed services as compared to their male counterparts. Both women and other gender adults were more likely to report multiple barriers to needed services than men including transportation and scheduling. This study is one of the largest to explore the service barriers of autistic adults by gender differences.